2021
DOI: 10.3389/fonc.2020.626751
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MYCN in Molecularly Defined Malignant Brain Tumors

Abstract: Misregulation of MYC genes, causing MYC overexpression or protein stabilization, is frequently found in malignant brain tumors highlighting their important roles as oncogenes. Brain tumors in children are the most lethal of all pediatric malignancies and the most common malignant primary adult brain tumor, glioblastoma, is still practically incurable. MYCN is one of three MYC family members and is crucial for normal brain development. It is associated with poor prognosis in many malignant pediatric brain tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 161 publications
(178 reference statements)
0
16
0
Order By: Relevance
“…Deregulation of MYC has been shown to stimulate and maintain tumorigenesis in ex vivo models [ 28 , 48 ]. MYC alterations are recurrently described amongst many different types of neoplasms, including pediatric brain tumors [ 6 , 25 ], with amplification being most frequently reported [ 25 , 28 ]. Glial and non-glial brain tumors harboring MYC amplification demonstrated a significantly worse prognosis [ 8 , 22 , 27 , 30 , 37 , 42 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of MYC has been shown to stimulate and maintain tumorigenesis in ex vivo models [ 28 , 48 ]. MYC alterations are recurrently described amongst many different types of neoplasms, including pediatric brain tumors [ 6 , 25 ], with amplification being most frequently reported [ 25 , 28 ]. Glial and non-glial brain tumors harboring MYC amplification demonstrated a significantly worse prognosis [ 8 , 22 , 27 , 30 , 37 , 42 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…MYCN-amplified SHH-MB is generally resistant to SMO inhibitors, a targeted therapy for SHH-MB [ 18 , 19 , 79 ]. It has been suggested that DFMO would have a greater effect on MYCN-amplified tumors [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall survival rates of the four MB subgroups were not significantly different ( Supplementary Figure S10 ), and SHH-MB was the most heterogeneous subgroup among the four MB subgroups [ 12 ]. SMO inhibition is a targeted therapy for SHH-MB, but SHH-MB patients with high MYCN expression were resistant to SMO inhibitors in general [ 18 , 19 , 79 ]. Furthermore, p53 mutations are associated with MYCN amplification and are implicated in conferring resistance to both radiation therapy and SMO inhibitors in SHH-MB [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, in multiple reports, that MYCN overexpression is directly associated with poor prognosis of neuroblastoma and it is thought that there is a strong correlation between gene overexpression and the evolutionary course of tumors [ 8 ]. On the other hand, MYCN has received less attention with respect to pediatric brain tumors, while recent reports have highlighted its role in the disease [ 9 , 10 , 11 ]. Apart from its role in neuroblastoma, MYCN has been studied in some extent for other pediatric brain neoplasms such as medulloblastoma [ 12 , 13 ], astrocytoma [ 14 ], glioblastoma [ 15 , 16 ], and others.…”
Section: Introductionmentioning
confidence: 99%
“…The MYCN oncogene is one of the most important genetic biomarkers for the diagnosis, prognosis and treatment of neuroblastoma. MYCN overexpression is associated with poor prognosis and rapid tumor growth [ 9 , 17 , 18 ]. However, it does not function as a unique f actor rather it is reported to participate in a network of other factors, procuring neuroblastoma’s pathology.…”
Section: Introductionmentioning
confidence: 99%